2005
DOI: 10.1002/path.1895
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tumour‐infiltrating lymphocytes and apoptosis in colitis‐associated neoplasia: comparison with sporadic colorectal cancer

Abstract: The development of colorectal cancer is a major complication for patients with chronic idiopathic colitis. Colitis-associated tumours tend to occur at a younger age and be more aggressive than sporadic colorectal cancers. While we have previously associated the presence of tumour-infiltrating lymphocytes (TILs) and increased apoptosis in sporadic colorectal cancer with high-level microsatellite instability and improved prognosis, little is known of the relationship between these variables in colitis-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…The only study so far that evaluated T cells in colitis-associated dysplasia compared to sporadic CRC using a quantified IHC method was conducted by Michael-Robinson et al . 16 . In that report, the counts of CD3 + and CD8 + cells were significantly higher in colitis-associated lesions than in sporadic cancer, which is contrary to our study.…”
Section: Discussionmentioning
confidence: 99%
“…The only study so far that evaluated T cells in colitis-associated dysplasia compared to sporadic CRC using a quantified IHC method was conducted by Michael-Robinson et al . 16 . In that report, the counts of CD3 + and CD8 + cells were significantly higher in colitis-associated lesions than in sporadic cancer, which is contrary to our study.…”
Section: Discussionmentioning
confidence: 99%
“…While increased TILs are associated with the MSI‐H phenotype,9, 10, 11 their relationship to apoptosis, cell proliferation and the prognosis is incompletely understood. Furthermore, colitis‐associated colon tumors arising in a background of inflammation have increased TILs but no associated increase in tumor cell apoptosis 15. Production of cytokines by TILs may regulate tumor cell growth and in this regard, TIL have been shown to secrete significant amounts of IFN‐γ 16.…”
mentioning
confidence: 99%
“…In one revealing study, Galon et al have demonstrated that simple measurements of CD3 and CD8 cell infiltration in the tumor core and invasive margin ( 68 ) of sporadic CRCs are superior to clinical TNM staging ( 69 ) and genetic microsatellite instability status ( 70 ) in predicting patient prognosis. The aberrant immune function that is characteristic of IBD may manifest itself in cancer immune-epithelium co-evolution: for example, IBD-CRC demonstrates greater lymphocyte infiltration compared to sporadic CRC, but with no associated prognostic improvement ( 71 ). This may be explained by impaired lymphocyte cytotoxicity in IBD, as reflected by reduced cancer cell apoptosis and lower granzyme B expression in lymphocytes infiltrating IBD-CRC compared to sporadic CRC.…”
Section: Common Selective Pressures In the Development Of Inflammatormentioning
confidence: 99%